Teacher performance on students learning outcomes in applied chemistry - Marnida Yusfiani (Jurnal Pendidikan Kimia (JPKim), 2020)
Teacher performance affect the students’ learning outcomes. End of semester instructional process evaluated by teacher and students. This study aimed to analyze the effect of Pedagogic, Professional, Personality, and Social as Teacher Performance on Students’ Learning Outcome in Applied Chemistry course. The population of this study is student’s took Applied Chemistry course which academic year is: 2017/2018 and 2018/2019 in Polytechnic of Tanjungbalai. The sampling is total sampling. Research method using Partial Least Square – Structural Equation Modelling (PLS – SEM). Questionnaire evaluation in the end of semester as instrument for Teacher Performance and Student’s assessment sheet as instrument for Students’ Learning Outcome. The result showed that there is a direct effect of negative and not significant correlation between Pedagogic and Social Teacher Performance on Students’ Learning Outcome Disclosure and there is a direct effect of positive and not significant between Professional and Personality Teacher Performance on Students’ Learning Outcome Disclosure. Keywords: Teacher performance; Learning outcomes; Applied chemistry; PLS – SEM